2021
DOI: 10.3390/antibiotics10050496
|View full text |Cite
|
Sign up to set email alerts
|

Initially Reduced Linezolid Dosing Regimen to Prevent Thrombocytopenia in Hemodialysis Patients

Abstract: This retrospective cohort study investigated the effects of an initially reduced linezolid dosing regimen in hemodialysis patients through therapeutic drug monitoring (TDM). Patients were divided into two groups depending on their initial dose of linezolid (standard dose of 600 mg every 12 h or initially reduced dose of 300 mg every 12 h/600 mg every 24 h). The cumulative incidence rates of thrombocytopenia and severe thrombocytopenia were compared between both groups using the Kaplan–Meier method and log-rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The C min of patients with eGFR <40 mL/min was significantly higher than that of patients with eGFR > 80 mL/min (OR: 4.273), whereas the C min of patients with an eGFR of 40–80 mL/min tended to be higher (OR: 2.109) ( 48 ). The hematological toxicity of linezolid in elderly patients with renal insufficiency may be related to drug overexposure ( 14 , 16 , 39 , 40 , 48 – 50 ).…”
Section: Expert Panel Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C min of patients with eGFR <40 mL/min was significantly higher than that of patients with eGFR > 80 mL/min (OR: 4.273), whereas the C min of patients with an eGFR of 40–80 mL/min tended to be higher (OR: 2.109) ( 48 ). The hematological toxicity of linezolid in elderly patients with renal insufficiency may be related to drug overexposure ( 14 , 16 , 39 , 40 , 48 – 50 ).…”
Section: Expert Panel Recommendationsmentioning
confidence: 99%
“…Patients with renal insufficiency can reach the goal of C min ≥ 2.0 mg/L with a 300 mg q12h regimen ( 18 ). Kawasuji et al ( 50 ) reported that the initial dose should be reduced to reduce the risk for linezolid-induced thrombocytopenia (LIT) in patients on HD.…”
Section: Expert Panel Recommendationsmentioning
confidence: 99%
“…Also, in patients undergoing haemodialysis, a dose reduction to 300 mg twice daily or 600 mg once daily has led to a linezolid trough concentration just before haemodialysis of 20.6 mg/L and 6.0 mg/L, respectively. Compared with a standard dose of 600 mg twice daily, less LIT was seen in this population [ 33 ]. This suggests that a dose reduction to 600 mg once daily is also appropriate in haemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well-established that LZD can cause myelosuppression; hence, complete blood cell counts should be monitored during LZD therapy. Moreover, surveillance for adverse events should be increased in the presence of other risk factors for myelosuppression, such as age, low body weight, renal impairment, or prolonged therapy [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%